Imputación penal de las personas jurídicas frente al fenómeno de la criminalidad organizada - Luggren, Rosana Elizabeth; Oroño, Néstor Antonio (Pontificia Universidad Católica del Perú, 2015)
Facing the phenomenon of organized crime, the criminal justice system for legal persons is confronted with the need to adapt the theoretical structures in order to provide an answer to the challenges rising from the high degree complexity and volatility, common qualities of the contemporary societies. t he modern legislations claim different solutions, such as the vicarious liability “act like someone else” or “be in someone else’s place”, which allows transferring the responsibility or guilt of a person. t his, among others, is recognized as a dual justice system. It is believed that a specific justice system for legal persons should be reached and, taking into account its peculiarities, make it coexist with the proper system for physical persons.

Frente al fenómeno de la criminalidad organizada, el sistema de imputación penal para las personas jurídicas se enfrenta con la necesidad de adecuar las construcciones teóricas a fin de brindar respuesta a los desafíos que emergen del alto grado de complejidad y volatilidad que caracteriza a las sociedades contemporáneas. e n las legislaciones modernas se han ensayado diversas soluciones, tales como el sistema vicarial “del actuar por otro” o “en lugar de otro”, que permite transferir a la persona jurídica la responsabilidad o culpabilidad de su representante; el reconocimiento de un doble sistema de imputación, entre otros. Creemos que debe avanzarse hacia un sistema específico de imputación para las personas jurídicas que atendiendo a sus particularidades coexista con el sistema propio para las personas físicas.
The criminal charges of legal persons against the phenomenon of organized crime
Keywords: Organized Crime; Legal Persons; Companies; Criminal Law; Criminalidad Organizada; Personas Jurídicas; Empresas; Derecho Penal; https://purl.org/pe-repo/ocde/ford#5.05.00